Effectiveness of nutrition education podcasts for behavior change among young adults in online food ordering - Fitra Maulida; Kartika Nugraheni; Ari Istianty; Ali Khomsan; Ali Rosidi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The rapid development of digital technology has driven an increase in the utilization of online food ordering services in Indonesia, particularly among young adults, who constitute 45% of the users. This trend presents nutritional challenges that necessitate intervention through digital media education. Podcasts are regarded as effective and accessible educational mediums; however, previous studies have primarily focused on their impact on knowledge and attitudes. This quasi-experimental study aimed to analyze the influence of podcast-based nutrition education on improving nutritional knowledge and altering online food ordering intentions, frequency of orders, and food choices. This study employed a pretest-posttest control group design involving 128 non-health students from Muhammadiyah University of Semarang (December 2024 to March 2025), divided equally into experimental and control groups. The experimental group received four podcast episodes, each under 10 minutes, over four weeks, whereas the control group received no intervention. Data were collected through pre- and post-test assessments and engagement evidence, with purposive sampling based on inclusion and exclusion criteria. Data analysis using the Mann-Whitney U test revealed significant improvements in nutritional knowledge (p < 0,001), changes in ordering intentions aligned with the Theory of Planned Behavior constructs (p < 0,001), decreased ordering frequency (p < 0,001), and healthier food choices (p < 0,001). In conclusion, the findings suggest that podcasts have the potential to be an innovative strategy in nutrition education to promote healthy eating habits in the digital era.